Origins and history of Chinese culture: views of their contemporaries - Uzhkenov, E. M.; Lytvynchuk, O. A. (Journal of Oriental Studies, 2016)
In this article the author writes about the culture of China in modern and ancient period. Also, the author describes the Confuciuos studies, which had influenced on modern business culture and changed the world outlook of Chinese people. The article is easy for understanding, because the literature style is easy, all expressions were studied by many scientists.